2017
DOI: 10.1002/jmv.24942
|View full text |Cite
|
Sign up to set email alerts
|

Clinical patterns associated with the concurrent detection of anti‐HBs and HBV DNA

Abstract: Simultaneous detection of anti-HBs and HBV DNA is a rare serological combination and has been described in acute and chronic HBV infection. To scrutinize viral and clinical patterns associated with concurrent detection of anti-HBs and HBV DNA. Simultaneous detection of anti-HBs and HBV DNA was observed in 64/1444 (4.4%) patients treated for HBV infection at the University Hospital of Essen from 2006 to 2016 (8 with acute, 20 with reactivated, and 36 chronic HBV infection). Clinical data and laboratory paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We have previously reported the occurrence of infections in healthy blood donors in which HBV DNA coexisted with anti‐HBs, highlighting the importance of molecular tests for the prevention of transmission of this infection in our region 5 . The coexistence of anti‐HBs and HBV DNA is a rare phenomenon and has been observed in acute, chronic, and reactivated HBV infections 11 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have previously reported the occurrence of infections in healthy blood donors in which HBV DNA coexisted with anti‐HBs, highlighting the importance of molecular tests for the prevention of transmission of this infection in our region 5 . The coexistence of anti‐HBs and HBV DNA is a rare phenomenon and has been observed in acute, chronic, and reactivated HBV infections 11 …”
Section: Discussionmentioning
confidence: 94%
“…5 The coexistence of anti-HBs and HBV DNA is a rare phenomenon and has been observed in acute, chronic, and reactivated HBV infections. 11 In several HBV-high endemic regions, blood donor screening includes the detection of anti-HBs. An optimal titer of anti-HBs (>200 mIU/mL) in blood components derived from donors with reactive anti-HBc and negative NAT DNA HBV has been set for the qualification of blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is less common than in those with isolated anti-HBc, it is important that all patients with anti-HBc positivity are screened for occult Anti-HBs = hepatitis B surface antibody; anti-HBe = hepatitis B 'e' antibody; anti-HBc = hepatitis B core antibody; HBeAg = hepatitis B 'e' antigen; HBsAg = hepatitis B surface antigen; HBV = hepatitis B virus; IVIG = intravenous immunoglobulin Apostolos Koffas, Grace E Dolman and Patrick TF Kennedy infection. 13 Paul et al recently showed that patients with resolved HBV infection receiving chemotherapy for haematological malignancies without antiviral prophylaxis, are at a decreased risk of HBVr when they have positive anti-HBs. 14 More recently, the virological marker Hepatitis B core-related antigen (HBcrAg) was reported to be associated with an increased risk of HBVr in HBsAg-negative and anti-HBc-positive subjects undergoing highrisk immunosuppressive regimens.…”
Section: Screeningmentioning
confidence: 99%
“…In serological markers of HBV infection, general theory considers that the antibody to HBsAg (anti-HBs) can neutralize HBsAg; therefore, it is generally agreed that there will be no simultaneous positive for both HBsAg and anti-HBs in routine clinical practice (14)(15)(16). However, the simultaneous presence of HBsAg and anti-HBs in chronic HBV carriers has been reported in previous studies (17,18).…”
Section: Introductionmentioning
confidence: 99%